Acetylcholinesterase from Puntius javanicus for the detection of carbamates and organophosphates - Sabullah M.K.; Ahmad S.A.; Shukor M.Y.; Shamaan N.A.; Khalid A.; Gansau A.J.; Dahalan F.A.; Sulaiman M.R. (SPB Pharma Society, 2024)
Indexed by SCOPUS